ANALISIS PENGELOLAAN DANA HAJI PADA PT. BANK ACEH SYARIAH - Zainul, Zaida Rizqi; Khairannis, Khairannis (EQUILIBRIUM, 2019)
Since the transfer of hajj funds from the Ministry of Religion to BPKH, BPKH has managed haj funds, one of which is by placing on Islamic bank products. The Islamic banks selected as managers and recipients of Hajj fund deposits are 31 Islamic banks. One of them is Bank Aceh Syariah. This study aims to determine the management of Hajj funds in Bank Aceh Syariah. The method used is descriptive analysis with a qualitative approach. The results of this study indicate that the management of Hajj funds at PT. Bank Aceh Syariah uses the wadiah yad dhamanah contract. Hajj funds at Bank Aceh Syariah are channeled to financing products so that they can be useful to increase profitability and maintain the liquidity of Aceh's banks. In addition, pilgrims also benefit in the form of returns from the management of the pilgrimage fund which is used to subsidize the pilgrimage departure funds of pilgrims.